ROS scavengers decrease γH2ax spots in motor neuronal nuclei of ALS model mice in vitro - Junghans, Maya; John, Felix; Cihankaya, Hilal; Schliebs, Daniel; Winklhofer, Konstanze F.; Bader, Verian; Matschke, Johann; Theiss, Carsten; Matschke, Veronika (Frontiers in Cellular Neuroscience, 2022)
Background: Amyotrophic lateral sclerosis (ALS) is an incurable neurodegenerative disease characterized by the loss of motor neurons in cerebral cortex, brainstem and spinal cord. Numerous studies have demonstrated signs of oxidative stress in postmortem neuronal tissue, cerebrospinal fluid, plasma and urine of ALS patients, without focusing on the specific processes within motor neurons. Thus, we aimed to investigate the relevance of reactive oxygen species (ROS) detoxification mechanisms and its consequences on the formation of toxic/lethal DNA double strand breaks (DSBs) in the ALS model of the Wobbler mouse. Methods: Live cell imaging in dissociated motor neuronal cultures was used to investigate the production of ROS using Dihydroethidium (DHE). The expression levels of ROS detoxifying molecules were investigated by qPCR as well as Western blots. Furthermore, the expression levels of DNA damage response proteins p53bp1 and H2ax were investigated using qPCR and immunofluorescence staining. Proof-of-principle experiments using ROS scavengers were performed in vitro to decipher the influence of ROS on the formation of DNA double strand breaks quantifying the γH2ax spots formation. Results: Here, we verified an elevated ROS-level in spinal motor neurons of symptomatic Wobbler mice in vitro. As a result, an increased number of DNA damage response proteins p53bp1 and γH2ax in dissociated motor neurons of the spinal cord of Wobbler mice was observed. Furthermore, we found a significantly altered expression of several antioxidant molecules in the spinal cord of Wobbler mice, suggesting a deficit in ROS detoxification mechanisms. This hypothesis could be verified by using ROS scavenger molecules in vitro to reduce the number of γH2ax foci in dissociated motor neurons and thus counteract the harmful effects of ROS. Conclusion: Our data indicate that maintenance of redox homeostasis may play a key role in the therapy of the neurodegenerative disease ALS. Our results underline a necessity for multimodal treatment approaches to prolong the average lifespan of motor neurons and thus slow down the progression of the disease, since a focused intervention in one pathomechanism seems to be insufficient in ALS therapy.